Cholecystokinin 1 Receptor – A Unique G Protein-Coupled Receptor Activated by Singlet Oxygen (GPCR-ABSO) - Jiang, Hong Ning; Li, Yuan; Jiang, Wen Yi; Cui, Zong Jie (Frontiers in Physiology, 2018)
Plasma membrane-delimited generation of singlet oxygen by photodynamic action with photosensitiser sulphonated aluminium phthalocyanine (SALPC) activates cholecystokinin 1 receptor (CCK1R) in pancreatic acini. Whether CCK1R retains such photooxidative singlet oxygen activation properties in other environments is not known. Genetically-encoded protein photosensitisers KillerRed or mini singlet oxygen generator (miniSOG) were expressed in pancreatic acinar tumor cell line AR4-2J, CCK1R, KillerRed or miniSOG were expressed in HEK293 or CHO-K1 cells. Cold light irradiation (87 mWatt.cm-2) was applied to photosensitier-expressing cells to examine photodynamic activation of CCK1R by Fura-2 fluorescent calcium imaging. When CCK1R was transduced into HEK293 cells which lack endogenous CCK1R, photodynamic action with SALPC was found to activate CCK1R in CCK1R-HEK293 cells. When KillerRed or miniSOG were transduced into AR4-2J which expresses endogenous CCK1R, KillerRed or miniSOG photodynamic action at the plasma membrane also activated CCK1R. When fused KillerRed-CCK1R was transduced into CHO-K1 cells, light irradiation activated the fused CCK1R leading to calcium oscillations. Therefore KillerRed either expressed independently, or fused with CCK1R can both activate CCK1R photodynamically. It is concluded that photodynamic singlet oxygen activation is an intrinsic property of CCK1R, independent of photosensitiser used, or CCK1R-expressing cell types. Photodynamic singlet oxygen CCK1R activation after transduction of genetically-encoded photosensitiser in situ may provide a convenient way to verify intrinsic physiological functions of CCK1R in multiple CCK1R-expressing cells and tissues, or to actuate CCK1R function in CCK1R-expressing and non-expressing cell types after transduction with fused KillerRed-CCK1R.